Effect of Brand Image and Halal Awareness on Interest in Buying Wardah Cosmetics in the City of Semarang - Sukma Anjani Susilowati; Makmun - Riyanto; Khairul - Saleh (Admisi dan Bisnis, 2023)
This research aim to determine the influence of Brand Image and Halal Awareness on Purchase Interest Wardah cosmetics in Semarang Region. The data collection method used in this research are literature review and  questionnaire. The questionnaire used is the Agree-Disagree Scale with a scale of 10. Sampling was done by using the incidental sampling method of 84 samples. Data processing was conducted using SPSS 22. Based on the calculation of multiple linear regression analysis, the equation Y = 2.970 + 0.451X1 + 0.392X2  is obtained,  and the results of the t test show that each variable accepts Ha1 and Ha2, so that the variables of Brand Image (X1) and Halal Awareness (X2) have a significant effect on the Purchase Interest (Y). The F test show that Ho3 is rejected and Ha3 is accepted, which means that the variables of Brand Image (X1) and Halal Awareness (X2) simultaneously influence the Purchase Interest (Y). Then the result of the determination coefficient test (R2) show a value of 0.724, which means that 72.4% of the Purchase Interest (Y) can be explained by the variables of Brand Image (X1) and Halal Awareness (X2) and the remaining 27.6% is influenced by others factors who were not included in this study.